WOMEN AND AIDS: THE ETHICS OF EXAGGERATED HARM - Mertz†, David (Bioethics, 1996)
This article examines the way in which some biomedical ethicists have constructed sexually transmitted AIDS as a significant threat to women's health. We demonstrate that the familiar claim that‘women are the fastest growing group'— whether of HIV-infected or of AIDS patients — is misleading because it obscures the distinction between proportional rate of growth and absolute increase. Feminist ethicists have suggested that misogyny of a male dominated health care system has led to underreporting of women AIDS cases in order to support these feminists’claim of AIDS being a real threat to women's health. Given the apparent rarity of tertiary transmissions of AIDS, the assertion that most or even many women are at significant risk for AIDS seem wrong. Particularly disturbing in this campaign is the fact that the theme of‘risky sex’has been extended all the way to lesbians, even though their risk to acquire AIDS sexually is non-existent to minuscule. We argue that actual harm is done to women by this exaggeration of their risk of contracting AIDS sexually. The scare has led to misappropriations of scarce health care funds. AIDS disproportionately affects women who inject drugs, and who suffer other diseases, poverty and malnutrition. It would have been better to concentrate health care efforts in this area instead of‘educating’women not at risk for AIDS how to prevent the acquisition of this disease. Unjustifiable AIDS anxiety has been created in women and has resulted in millions of unnecessary HIV-tests, and many broken relationships. This anxiety has inevitably reduced the pleasure of having sex for many women. We reject the kind of‘victim ideology’that lies at the heart of this strategy which has, unfortunately, been supported by a number of influential feminist ethicists.